2019
DOI: 10.1088/1757-899x/628/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and surface properties of hydrogenated amorphous silicon-germanium thin films prepared by LF-PECVD

Abstract: We studied the surface morphology and biocompatibility of hydrogenated amorphous silicon-germanium (a-Si1-xGex:H) thin films prepared by Low Frequency Plasma Enhanced Chemical Vapor Deposition (LF-PECVD). These films were deposited on a Corning 2947 glass substrate having a thickness of 3 μm, the electrical performance showed a decreased electrical resistance for low regime voltage. The root mean square (RMS) surface roughness of the films was measured by atomic force microscopy (AFM) in a non-contact mode. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The electrode showed at least 10× reduction in electrochemical impedance, ~7% transmittance improvement, and stability after over 600 cycles of mechanical bending (Yang et al, 2019b ). Other semiconducting materials, such as germanium (Ge), silicon germanium alloy (SiGe), indium-doped zinc oxide (IZO), indium-gallium-zinc oxide (a-IGZO), and zinc oxide (ZnO), has also been investigated as recording electrode materials because of their desired electrical, mechanical, optical, biocompatible, and stable/biodegradable properties (Gao et al, 2012 ; Dagdeviren et al, 2013 ; Lee et al, 2015 ; Gutierrez-Heredia et al, 2017 ; Mao et al, 2018 ; Huerta et al, 2019 ).…”
Section: Electrode Materialsmentioning
confidence: 99%
“…The electrode showed at least 10× reduction in electrochemical impedance, ~7% transmittance improvement, and stability after over 600 cycles of mechanical bending (Yang et al, 2019b ). Other semiconducting materials, such as germanium (Ge), silicon germanium alloy (SiGe), indium-doped zinc oxide (IZO), indium-gallium-zinc oxide (a-IGZO), and zinc oxide (ZnO), has also been investigated as recording electrode materials because of their desired electrical, mechanical, optical, biocompatible, and stable/biodegradable properties (Gao et al, 2012 ; Dagdeviren et al, 2013 ; Lee et al, 2015 ; Gutierrez-Heredia et al, 2017 ; Mao et al, 2018 ; Huerta et al, 2019 ).…”
Section: Electrode Materialsmentioning
confidence: 99%
“…Previous studies showed that DLC coatings had superior biocompatibility and cell attachment properties in several cell line such as osteoblast, fibroblast, and keratinocytes cell cultures 40–42 . Moreover, geranium based surface modifications were claimed that they have biocompatible properties and these materials did not stimulate toxic features for cell cultures 37,43,44 . In parallel with the literature, DLC–Ge coating supported cell growth and attachment in a favorable manner that cell survival ratio was analyzed to have similar properties to (−) Control with 95% cell viability rate (Figure 3).…”
Section: Resultsmentioning
confidence: 66%
“…[40][41][42] Moreover, geranium based surface modifications were claimed that they have biocompatible properties and these materials did not stimulate toxic features for cell cultures. 37,43,44 In parallel with the literature, DLC-Ge coating supported cell growth and attachment in a favorable manner that cell survival ratio was analyzed to have similar properties to (À) Control with 95% cell viability rate (Figure 3). After 24 h of seeding, fibroblast cell culture spread was found favorable on the GE-DLC coating compared to uncoated borosilicate glass surface ([+] Control) which was investigated by using Hoechst 33258 fluorescent staining (Figure 4).…”
Section: Structural and Morphological Characterizationmentioning
confidence: 85%
“…In recent years, silicon–germanium (SiGe) films such as hydrogenated amorphous SiGe (a-SiGe:H) and hydrogenated microcrystalline SiGe (μc-SiGe:H) have been known as potential materials for thin-film solar cells, microelectromechanical systems (MEMS), and biomedical applications. In the semiconductor industry field, a surface channel in a metal-oxide-semiconductor field-effect transistor (MOSFET) with a graded SiGe film enhanced electron mobility due to the tensile strain . Thermal chemical vapor deposition (CVD) above 1000 °C is used for high-quality film, whereas plasma-enhanced chemical vapor deposition (PECVD) with a lower temperature and a high deposition rate of up to 200 nm/min is used for a thick film. ,, …”
Section: Introductionmentioning
confidence: 99%